PENGARUH MAQASHID SYARIAH DAN ISLAMIC SOCIAL REPORTING TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Syurmita, Syurmita; Kurniawan, Rizky Fernanda; Rahmi, Asri Noer; Welkom, Syahfitri Suryaningsi; Rachman, M. Emil (AGROTEKSOS; Vol 34 No 3 (2024): Jurnal Agroteksos Desember 2024DO - 10.29303/agroteksos.v34i3.1226, 2024)
This research is motivated by the rapid growth of Islamic banking, which necessitates that Islamic banks enhance profitability to operate in a sound and efficient manner in line with Sharia principles. In their operations, Islamic banks focus not only on financial aspects but also on non-financial aspects, such as Maqashid Shariah and Islamic Social Reporting (ISR). This study aims to examine the impact of Maqashid Shariah and ISR on the profitability of Islamic banks. A quantitative method is used, with a population of Islamic commercial banks in Indonesia from 2018 to 2022. The sample was selected using purposive sampling, resulting in data from 55 annual reports of Islamic banks. The analytical technique used is multiple linear regression to measure the influence of each variable. The findings show that Maqashid Shariah has a significant negative effect on profitability (t-value of -4.468 and a significance value < 0.001). This result aligns with the concept of Maqashid Shariah in banking, where the primary goal of Islamic banks is not short-term profit but rather social welfare. On the other hand, ISR has a significant positive effect on profitability (t-value of 4.308 and a significance value < 0.001). ISR plays an important role in strengthening the image, reputation, and public trust in Islamic banks. This study provides insight into the importance of non-financial aspects in supporting the sustainability of Islamic banks.